Field occupancy by breeding lapwings Vanellus vanellus and redshanks Tringa totanus in agricultural wet grasslands - Durant, Daphné; Tichit, Muriel; Fritz, Hervé; Kerneis, Eric (Agriculture, Ecosystems & Environment, 2008)
This study is based on a comparative approach to explore how two breeding waders, the lapwing Vanellus vanellus and the redshank Tringa tetanus, respond to cattle grazing in terms of timing and intensity of grazing in the Marais Poitevin (French Atlantic coast). Generalised linear mixed models (GLMM) showed that the two main predictors determining suitable grasslands were sward structure (i.e. mean sward height and tussock frequency) and water surface. A grazing index (LU.days/ha) was then monitored to tackle the extent to which the occupancy of fields by waders depended upon the grazing management involved in previous autumn, as well as in spring (early and mid-spring grazing). Species’ biology as well as variations in their sward structure requirements may explain why they responded differently to grazing. In the lapwing, a precocious species which nests in short swards (≤ 10 cm) with no/few tussocks, the suitability of grasslands was (at least partly) driven by both delayed (previous autumn) and direct (early spring) effects of grazing. Conversely, the redshank, which nests later and needs taller swards (10-40 cm) did not respond to autumn grazing, but seemed to be more sensitive to mid-spring grazing. Stocking densities (in LU/ha) in spring were also calculated to examine whether, due to potential risks of nest trampling and/or direct disturbance caused by livestock, birds avoided heavily grazed grasslands. Contrary to what was expected, the lapwing and the redshank responded positively to early spring and mid-spring stocking densities, respectively. These results are discussed in the light of the habitat characteristics and the grazing management situation of the study site, as well as their usefulness for the design of agri-environmental schemes.